2014
DOI: 10.1063/1.4861467
|View full text |Cite
|
Sign up to set email alerts
|

A cascade through spin states in the ultrafast haem relaxation of met-myoglobin

Abstract: We report on a study of the early relaxation processes of met-Myoglobin in aqueous solution, using a combination of ultrafast broadband fluorescence detection and transient absorption with a broad UV-visible continuum probe at different pump energies. Reconstruction of the spectra of the transient species unravels the details of the haem photocycle in the absence of photolysis. Besides identifying a branching in the ultrafast relaxation of the haem, we show clear evidence for an electronic character of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 43 publications
9
51
0
Order By: Relevance
“…A further-redshifted tail disappears on a much faster timescale, ≈ 300 fs (Fig. 2c); as extensively discussed in the literature, these TA features are compatible with either the existence of intermediate electronic species 7,14,21,23,24 or with a hot ground state vibrational relaxation pathway 8,10 , as illustrated in Fig. 1b.…”
Section: Figsupporting
confidence: 54%
See 1 more Smart Citation
“…A further-redshifted tail disappears on a much faster timescale, ≈ 300 fs (Fig. 2c); as extensively discussed in the literature, these TA features are compatible with either the existence of intermediate electronic species 7,14,21,23,24 or with a hot ground state vibrational relaxation pathway 8,10 , as illustrated in Fig. 1b.…”
Section: Figsupporting
confidence: 54%
“…In particular, owing to the difficulties to experimentally achieve simultaneous structural sensitivity and time resolution, contrasting hypotheses (schematically depicted in Fig. 1b) have been put forward for the dynamics at 50 fs < t < 5 ps with respect to the possible contributions of intermediate heme electronic states 7,8,10,14,17,19,[21][22][23][24][25] . To be able to address these issues we developed a novel Femtosecond Stimulated Resonance Raman setup (FSRRS) that uniquely combines high temporal precision and frequency resolution with fine tunability all over the heme proteins absorption spectrum.…”
mentioning
confidence: 99%
“…It was concluded that the generated cyt c photo-product corresponds to the photo-dissociated heme 19 based on the similarity of its transient signal with the 5-coordinated (5-c) MP-8 spectrum that is structurally analogous to the 5-c cyt c. Assuming that the broad and red-shifted spectrum, in respect to the oxidized species, along with the "dip" on the red-side of the -band are signatures of the 5-c photo-product, we conclude that the c 1 -hemes in the bc 1 complex also undergo photo-dissociation of one of their axial ligand. The life time matches the 5-7 ps reported for the photo-cycle of a variety of 6-c hemes proteins, including cyt c. 11,15,17,19 All these reports are unanimous in assigning this time constant to the rebinding of the photo-dissociated ligand. It should be mentioned that the 5.4-ps DADS might not be entirely free from other processes as vibrational cooling has previously been monitored with a life-time of ~4.6 ps.…”
supporting
confidence: 52%
“…The ultrafast behaviors, and more specifically, the relaxation of photo-excited hemes, has indeed been the object of intense study since the late 1980s. 11,12 For example, the hemes in cyt c and cyt b 5 , which are structurally comparable to the c 1 -and b-hemes of the bc 1 complex, respectively, 13,14 are known to dissociate from their axial ligand within femtoseconds as a response to light absorption. [14][15][16] While the early steps of the heme photo-cycle still raises questions, it is generally accepted that photoexcitation of the heme is followed by an electron transfer (ET) to the iron d-orbitals, 16 which in turn is believed to trigger the ligand dissociation in ferrous complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrafast behaviours, and more specifically, the relaxation of photo-excited hemes, have indeed been the object of an intense study since the late 1980s. 9,10 For example, the ferrous b-hemes in the homologous cyt bc 1 complex have been found to undergo efficient photo-dissociation and -oxidation within femtoseconds after visible light excitation. 11 While photodissociation seems to be a rather standard feature in hemeembedded proteins, 9, 12 the initiation of a charge separated state is intriguing within a complex that is directly involved in cross-membrane proton-coupled-electron transfer.…”
Section: Introductionmentioning
confidence: 99%